Spectrophotometric Determination of Hemoglobin with Lanthanum(III)-(DBC-Arsenazo) - Zhai, Qing-Zhou; Zhang, Xiao-Xia (Asian Journal of Chemistry, 2010)
A spectrophotometric determination of hemoglobin was proposed with lanthanum(III)-(DBC-arsenazo) complex as a spectrum probe in the presence of emulgent OP. In a Britton- Robinson buffer at pH 2.9, hemoglobin, La(III) and DBCarsenazo form a colour compound. At its maximum absorption wavelength of 364 nm, the apparent molar absorptivity for the determination of hemoglobin is ε364 nm = 3.59 × 105 L mol-1 cm-1. The linear relationship between the concentration of hemoglobin and its absorbance exists over the concentration range of 10-70 mg L-1 of hemoglobin and Beer's law is obeyed. The proposed method was directly used in the determination of total proteins in human serum samples with satisfactory results.